Measuring 3D shape in orthodontics through geometric morphometrics - Luis Huanca Ghislanzoni; Roberta Lione; Paola Cozza; Lorenzo Franchi (SpringerOpen, 2017)
Abstract Background Geometric morphometrics (GMM) has been traditionally applied to the field of biology to study developmental differentiations between species. Orthodontics deals with the shape and size of the face and its components. While several tools have been used to measure size, proportions, and relations between anatomical components, shape has been mainly described by esthetic criteria. The purpose of this paper is to present methods to measure shape of 3D orthodontic data, beyond the conventional tools that have been traditionally used in cephalometrics and in facial and dental cast analysis. Findings The authors showcase an example of applying geometric morphometrics to measure palates from scanned dental casts. GMM can be used as a useful tool to describe the three-dimensional shape of surfaces of orthodontic interest. A general introduction to the theoretical principles of how to apply GMM is provided. Conclusions Variability can be measured through the Principal Component Analysis (PCA) and can lead to the identification of shape patterns and sources of variability of the shape, independently from changes in size.